2014
DOI: 10.1007/s13197-014-1486-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of β-galactosidase from streptococcus thermophilus for galactooligosaccharides synthesis

Abstract: Efficiency of different methods for disruption of Streptococcus thermophilus cells, isolated from different dairy products, to release β-galactosidase and synthesis of GOS by extracted enzyme using whey supplemented with different concentrations of lactose as a substrate was studied. Unlike most other studies on GOS synthesis which used only one method of cell disruption and only few microbial strains, we compared five different cell disruption methods and used 30 strains of S. thermophilus in order to find ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 40 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Ranjana et al (2011) proposed a method for using lactose from whey to produce GOS by using the β-galactosidase from Bacillus circulans in batch reactor and in recycle membrane reactor; the authors observed better results with the latter method (33 % higher production) obtaining 77 % of pure GOS. Sangwan et al (2014) reported that the S. thermophilus β-galactosidase could produce GOS in an appreciable amount (53.45 g/L) using lactose-supplemented whey as substrate. This amount was obtained using a total of 30 % lactose concentration and 10 U/mL of enzyme after 5 h at 40°C and pH 6.8.…”
Section: Galactooligosaccharidesmentioning
confidence: 99%
“…Ranjana et al (2011) proposed a method for using lactose from whey to produce GOS by using the β-galactosidase from Bacillus circulans in batch reactor and in recycle membrane reactor; the authors observed better results with the latter method (33 % higher production) obtaining 77 % of pure GOS. Sangwan et al (2014) reported that the S. thermophilus β-galactosidase could produce GOS in an appreciable amount (53.45 g/L) using lactose-supplemented whey as substrate. This amount was obtained using a total of 30 % lactose concentration and 10 U/mL of enzyme after 5 h at 40°C and pH 6.8.…”
Section: Galactooligosaccharidesmentioning
confidence: 99%
“…GOS was prepared in our laboratory using bgalactosidase extracted from native strain of S. thermophilus (Sangwan, Tomar, Ali, Singh, & Singh, 2014). Whey supplemented with lactose was used as a cost effective substrate for the production.…”
Section: Discussionmentioning
confidence: 99%
“…While Geiger et al. () reported a yield of 34%, Sangwan, Tomar, Ali, Singh, and Singh () detected no GOS formation at all (Table , no. 86 and 87).…”
Section: Gos Synthesis In Milk and Wheymentioning
confidence: 94%
“…References: a: Prenosil et al, ; b: Fischer & Kleinschmidt, ; c: Mause, ; d: Jovanovic‐Malinovska, Fernandes, Winkelhausen, & Fonseca, ; e: Valero, ; f: Rodriguez‐Colinas et al, ; g: Gosling et al, ; h: Rodriguez‐Colinas, Poveda, Jimenez‐Barbero, Ballesteros, & Plou, ; i: Cho et al, ; j: Hellerová & Čurda, ; k: Pocedičová et al, ; l: Splechtna et al, ; m: Vasiljevic & Jelen, ; n: Lopez Leiva & Guzman, ; o: Wierzbicki & Kosikowski, ; p: Sen, Nath, Bhattacharjee, Chowdhury, & Bhattacharya, ; q: Sen, Bhattacharjee, & Bhattacharya, ; r: Geiger et al, ; s: Rustom, Foda, & López‐Leiva, ; t: Hugo, Bruno, & Golowczyc, ; u: Golowczyc et al, ; v: Sabater, Olano, Prodanov, Montilla, & Corzo, ; w: Manucci, ; x: Adamczak, Charubin, & Bednarski, ; y: Foda & Lopez‐Leiva, ; z: Padilla et al, ; aa: Sangwan et al., ; ab: Lisboa et al., ; ac: Song et al., ; ad: Čurda, Rudolfová, Štětina, & Dryák, ; ae: Frenzel et al., ; af: Chen et al., ; ag: Zerge, ; ah: Lorenzen et al., ; ai: Pruksasri & Supee, ; aj: Rodriguez‐Colinas et al., ; ak: Mozaffar et al., ; al: Bakken, Hill, & Amundson, ; am: Foda, Kholif, & Kholif, ; an: Burvall et al., ; ao: Greenberg & Mahoney, ; ap: Roy et al., ; aq: Yadav et al., , ar: Liu et al., , as: Lisboa et al., , at: Roberts & Pettinati, , au: Ruiz‐Matute et al., , av: Patent No. EP 0 323 201 B1, 1990, aw: Goulas et al., .…”
Section: Gos Synthesis In Milk and Wheymentioning
confidence: 99%